Formulasi Kombinasi Optimum Faktor-faktor Produksi Usaha Peternakan Sapi Perah Rakyat di Kabupaten Boyolali - Erlyna Wida (Universitas Sebelas Maret (UNS), 2008)
The aims of this research are to 1) knowing the level of use optimum input which can yield maximum income by constraints konsentrat, bekatul, hijauan, capital, and other input, 2) Knowing change of optimal income in the change of pakan price, fresh milk price and anakan price Basic method used in this research is descriptive. Determination of research area is purposive that is Boyolali Regency with subdistrict Musuk. And than taken one village is Sukorejo. Farmer taken as sample in this research are farmer have adult dairy cattle. Taken respondent with simple random sampling is 40 respondent farmer of dairy cattle. Result of research indicate that maximal income which can be reached in effort ranch of scale people dairy cattle 4 tail per UT equal to Rp Rp 4.003.592 with combination result of effort in the form of ox anakan counted 3 tail, milk counted 8.700 litre, and compost counted 15.000 kg. Using input in the form of consentrat equal to 4.700 kilogram, bekatul counted 1.839 kg, waste of soybean cake counted 2.053 kg, hijauan counted 20.440 kg. In used of resources used up and no remains. Result of sensitivitas analysis indicate that optimal income of dairy cattle livestock are sensitive to a) increasing price of fresh milk, anakan, input and compost togetherly equal to 5% and 10%, b) decreasing price of output equal to 5% and 10% at fixed cost, c) increasing price of consentrat equal to 5 - 10% at the fix price of output. Key words : optimal combination, dairy cattle, sensitivity